2019
DOI: 10.1155/2019/9278432
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Uptake of Intermittent Preventive Treatment of Malaria in Pregnancy: A Cross-Sectional Study in Private Health Facilities in Tema Metropolis, Ghana

Abstract: Introduction. Intermittent preventive treatment of malaria in pregnancy with sulfadoxine pyrimethamine (IPTp-SP) is effective in preventing the adverse consequences of malaria on birth outcomes. Methods. A cross-sectional survey was carried out among antenatal and postnatal women and midwives at private health facilities in Tema using the mixed method to investigate factors associated with uptake of IPTp-SP. Antenatal and postnatal women were consecutively enrolled and data on their sociodemographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 25 publications
(39 reference statements)
10
33
2
Order By: Relevance
“…Moreover, the adjusted odds ratio results indicate that pregnant women who attended ANC three times only and those who visited ANC oneor two-times only during gestation period had lower odds of receiving optimal doses of IPTp-SP compared to pregnant women who had made four or more ANC visits. This finding is consistent with studies done in Malawi [30,31], Uganda [49], Tanzania [22,33], Ghana [36,39], Burkina Faso [34], Mali [35,37], Cameroon, and in Benin [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the adjusted odds ratio results indicate that pregnant women who attended ANC three times only and those who visited ANC oneor two-times only during gestation period had lower odds of receiving optimal doses of IPTp-SP compared to pregnant women who had made four or more ANC visits. This finding is consistent with studies done in Malawi [30,31], Uganda [49], Tanzania [22,33], Ghana [36,39], Burkina Faso [34], Mali [35,37], Cameroon, and in Benin [32].…”
Section: Discussionsupporting
confidence: 92%
“…This estimate is reflected in a study by Nkoka et al that used MDHS dataset [31]. Globally, studies have revealed that uptake of at least two doses of IPTp-SP is associated with number of ANC visits [5,22,[30][31][32][33][34][35][36][37][38][39], directly observed therapy (DOT) [5,30,38,40,41], residential area [22,30,42], age of woman [42], education level and socioeconomic status [43], parity [5,42], timing of initial ANC visit [5,31,44], knowledge about malaria/IPTp-SP [5,38] and stockouts of the commodity [5,38,45]. This study aimed to contribute to identifying factors associated with completion of recommended doses of SP during pregnancy post-adoption of the updated WHO policy in resource-limited settings from a nationally representative sample.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the adjusted odds ratio results indicate that pregnant women who attended ANC three times only and those who visited ANC one-or two-times only during gestation period had lower odds of receiving optimal doses of IPTp-SP compared to pregnant women who had made four or more ANC visits. This finding is consistent with studies done in Malawi [30,31], Uganda [49], Tanzania [22,33], Ghana [36,39], Burkina Faso [34], Mali [35,37], Cameroon, and in women who managed at least four ANC visits [20].…”
Section: Discussionsupporting
confidence: 90%
“…This estimate is reflected in a study by Nkoka et al that used MDHS dataset [31]. Globally, studies have revealed that uptake of at least two doses of IPTp-SP is associated with number of ANC visits [5,22,[30][31][32][33][34][35][36][37][38][39], directly observed therapy (DOT) [5,30,38,40,41], residential area [22,30,42], age of woman [42], education level and socioeconomic status [43], parity [5,42], timing of initial ANC visit [5,31,44], knowledge about malaria/IPTp-SP [5,38] and stockouts of the commodity [5,38,45].…”
Section: Ninety-eight Percent Of Malaria Infections Are Caused By Plamentioning
confidence: 99%
“…This nding was comparable with the study reported from Kenya (25) which shows that poor individuals were less likely to use any kind antimalarial drugs for pregnant women. Other studies in some developing countries indicated that IPTp use during pregnancy was concentrated among women in the richest households (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%